Muscular system coordination - Aceski, Aleksandar; Tufekchievski, Aleksandar; Vuksanovikj, Vladimir; Spasovska, Katerina (Faculty of physical education sport and health, 2018)
The muscle is a very complex system where bioelectric potential is transformed into biochemical, and biochemicalinto biomechemical, whereby a movement is allowed. Both elementary and complex movements are performed through constant coordinated action of muscles. Knowing the coordination of the muscular system while performing movements is essential for proper planning, programming, implementation of physical activity, as well as determining the effects of the application of physical exercise.
Keywords: agonist; antagonist; fixator; neutralizer; physical exercise; motion